Ethical issues in resuscitation and intensive care medicine. Issue 1 (January 2016) - Modra, Lucy; Hilton, Andrew
Abstract: Intensive care medicine is richly endowed with ethical dilemmas, including decision making on behalf of incompetent patients, withdrawal of treatment decisions and rationing of limited resources. Intensive care physicians need to be attuned to these ethical aspects of their practice. Beauchamp and Childress' four principles of medical ethics provide a useful approach to ethical problems. However, the principles provide a framework rather than an 'answer'. The advent of ECMO-CPR illustrates some common ethical dilemmas in intensive care medicine.